2003
DOI: 10.1038/sj.sc.3101534
|View full text |Cite
|
Sign up to set email alerts
|

Effect of training intensity on physical capacity, lipid profile and insulin sensitivity in early rehabilitation of spinal cord injured individuals

Abstract: Study design: Pre-post training intervention. Objectives: To evaluate the effect of training intensity on physical capacity, lipid profile and insulin sensitivity in early rehabilitation of spinal cord injured (SCI) patients, and to assess the correlation between peak aerobic capacity (VO 2Peak ) and insulin sensitivity. Setting: Spinal Cord Rehabilitation Unit, Sunnaas Hospital, Nesoddtangen, Norway. Method: Six recently injured SCI individuals participated in the arm training intervention and were randomly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
108
0
10

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(125 citation statements)
references
References 29 publications
7
108
0
10
Order By: Relevance
“…11 Participants training at a high intensity (70-80% HR reserve) showed a significantly greater improvement in VO 2peak compared with those training at a low intensity (40-50% HR reserve) over 8 weeks. 12 Injury level seems important in predicting change in VO 2max . Hjeltnes et al 13 found participants with paraplegia had a 28% increase in peak oxygen uptake throughout the B4-month training period, but there was no change in those with tetraplegia.…”
Section: Resultsmentioning
confidence: 99%
“…11 Participants training at a high intensity (70-80% HR reserve) showed a significantly greater improvement in VO 2peak compared with those training at a low intensity (40-50% HR reserve) over 8 weeks. 12 Injury level seems important in predicting change in VO 2max . Hjeltnes et al 13 found participants with paraplegia had a 28% increase in peak oxygen uptake throughout the B4-month training period, but there was no change in those with tetraplegia.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, high-intensity upper-body physical activity has been shown to improve insulin sensitivity. 7 However, none of these studies included an AB comparison group. 1,4,7 It is probable that the young age and high level of training of our subjects impacted our findings.…”
Section: Discussionmentioning
confidence: 99%
“…7 However, none of these studies included an AB comparison group. 1,4,7 It is probable that the young age and high level of training of our subjects impacted our findings. The use of MRI to measure body composition has been shown to be of particular relevance in assessing muscle quality and adipose tissue in the SCI population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The only included study that involved random assignment of subjects to an intervention compared high-intensity vs low-intensity exercise (26). Only 3 subjects were assigned to each group, and no control group was included for comparison.…”
Section: Resultsmentioning
confidence: 99%